C2N: an excellent two-dimensional monolayer membrane for He separation. Issue 42 (29th September 2015) - Zhu, Lei; Xue, Qingzhong; Li, Xiaofang; Wu, Tiantian; Jin, Yakang; Xing, Wei
Abstract : Using the first-principles density functional theory (DFT) and molecular dynamics (MD) simulations, we investigate the He separation performance of a porous C2 N monolayer synthesized recently. Abstract : Using the first-principles density functional theory (DFT) and molecular dynamics (MD) simulations, we investigate the He separation performance of a porous C2 N monolayer synthesized recently. The DFT calculations demonstrate that the porous C2 N monolayer is stable enough to be used as a gas separation membrane and the porous C2 N monolayer with a suitable pore size presents a surmountable energy barrier (0.13 eV) for He molecules passing through the membrane. Furthermore, the porous C2 N monolayer shows an exceptionally high selectivity for He/Ne (Ar, CH4, CO2, N2, etc. ) in a wide range of temperatures. Besides, using MD simulations we demonstrate that the porous C2 N monolayer exhibits a He permeance of 1 × 10 7 GPU at room temperature, which is much higher than the value (20 GPU) in current industrial applications. Therefore, the porous C2 N monolayer should be an excellent candidate for He separation from natural gas, due to its high selectivity and excellent permeability.